Jawaban atas pertanyaan-pertanyaan Komisi X DPR-RI dalam rapat dengar pendapat dengan LIPI tanggal 29 Januari 1991 (Lembaga Ilmu Pengetahuan Indonesia, 1991)
Response of the head of Indonesian Council of Sciences to questions raised in the 10th Commission on science and research activities in Indonesia.